Hyperemesis gravidarum in the Medical Birth Registry of Norway - a validity study - Vikanes Åse; Magnus Per; Vangen Siri; Lomsdal Sølvi; Grjibovski Andrej M (BMC, 2012)
Abstract Background Valid registration of medical information is essential for the quality of registry-based research. Hyperemesis gravidarum (HG) is characterized by severe nausea and vomiting, weight loss and electrolyte imbalance starting before 22nd gestational week. Given the fact that HG is a generally understudied disease which might have short- and long- term health consequences for mother and child, it is of importance to know whether potential misclassification bias influences the results of future studies. We therefore assessed the validity of the HG-registration in the in Medical Birth Registry of Norway (MBRN) using hospital records. Methods The sample comprised all women registered in MBRN with HG and who delivered at Ullevål and Akershus hospitals in 1.1.-31.3.1970, 1.4.-30.6.1986, 1.7.-30.9.1997 and 1.10.-31.12.2001. A random sample of 10 women per HG case, without HG according to MBRN, but who delivered during the same time periods at the same hospitals was also collected. The final sample included 551 women. Sensitivity, specificity, positive and negative predictive values (PPV and NPV) were estimated using strict and less strict diagnostic criteria of HG, indicating severe and mild HG, respectively. Hospital journals were used as gold standard. Results Using less strict diagnostic criteria of HG, sensitivity, specificity, PPV and NPV were 83.9% (95% CI: 67.4-92.9), 96.0% (95% CI: 93.9-97.3), 55.3% (95% CI: 41.2-68.6) and 99.0% (95% CI: 97.7-99.6), respectively. For strict diagnostic criteria, being hospitalised due to HG the corresponding values were 64% (95% CI: 38.8-87.2), 92% (95% CI: 90.2-94.6), 18.6% (95% CI: 10.2-31.9) and 99.0% (95% CI: 97.7-99.6). Conclusions The results from our study are comparable to previous research on disease registration in MBRN, and show that MBRN can be considered valid for mild HG but not for severe HG.